2009
DOI: 10.1211/jpp.61.02.0014
|View full text |Cite
|
Sign up to set email alerts
|

Animal studies supporting the inhibition of mast cell activation by Eriobotrya japonica seed extract

Abstract: These results suggest that Eriobotrya japonica seed extract may contribute to the relief of allergic disease-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This wide spectrum of biological activity has been attributed largely to loquat contents of antioxidant compounds such as flavonoids and polyphenols, in addition to the presence of triterpenes, glycosides, and sesquiterpenes. 3, 5 For example, several kinds of flavonoids, epicatechin, epicatechin gallate, methyl chlorogenate, cinchonain as well as quercetin, isoquercetin, quercetin-glycoside, and kaempferol glycosides have been isolated from loquat seed, leaf, and fruit. Ferreres et al and others showed that loquat leaves, flowers, and fruits contain flavonoids and polyphenols and their contents exhibited a positive correlation with their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…This wide spectrum of biological activity has been attributed largely to loquat contents of antioxidant compounds such as flavonoids and polyphenols, in addition to the presence of triterpenes, glycosides, and sesquiterpenes. 3, 5 For example, several kinds of flavonoids, epicatechin, epicatechin gallate, methyl chlorogenate, cinchonain as well as quercetin, isoquercetin, quercetin-glycoside, and kaempferol glycosides have been isolated from loquat seed, leaf, and fruit. Ferreres et al and others showed that loquat leaves, flowers, and fruits contain flavonoids and polyphenols and their contents exhibited a positive correlation with their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%